2006
DOI: 10.1007/s11661-006-0162-3
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical behaviors of chromium- or niobium-modified Ni47.5Al25Fe27.5 alloy at elevated temperature

Abstract: The microstructure of the Ni 47.5 Al 25 Fe 27.5 alloy was modified by adding Cr or Nb to improve its tensile properties. Increasing the Cr content increased the volume fraction of the interdendritic regions and, subsequently, increased the tensile elongation at room temperature. Additionally, adding Nb significantly improved the tensile properties of the Ni 47.03 Al 24.75 Fe 27.23 Nb 1 alloy, because the element Nb reduces the number of ␥/␤Ј interfaces and strengthened both the ␥ and ␤Ј phases and the ␥/␤Ј int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
1
1
Order By: Relevance
“…A relative high strength as well as ductile mechanical behavior (Yield strength ~ 900 MPa, UTS~1320 MPa, and ε~8%, respectively) can be obtained at the strain rate of 8 × 10 -5 s -1 . The yield strength is 30% higher than the yield strength (650 MPa) of the as-cast alloy which reported previously by Tsau et al 11 . This improvement of yield strength is suggested to be contributed by the refined microstructure from the TMT, eliminating the dendritic structure and refining the precipitate.…”
Section: Resultscontrasting
confidence: 52%
See 1 more Smart Citation
“…A relative high strength as well as ductile mechanical behavior (Yield strength ~ 900 MPa, UTS~1320 MPa, and ε~8%, respectively) can be obtained at the strain rate of 8 × 10 -5 s -1 . The yield strength is 30% higher than the yield strength (650 MPa) of the as-cast alloy which reported previously by Tsau et al 11 . This improvement of yield strength is suggested to be contributed by the refined microstructure from the TMT, eliminating the dendritic structure and refining the precipitate.…”
Section: Resultscontrasting
confidence: 52%
“…Furthermore, Ishida et al investigated the Ni-Al-X alloys 6 and found that the third element of Fe or Cr preferred to form the γ phase rather than β (bcc)and γ' phases, and Nb preferred to form the γ' phase rather than the β and γ phases. More recently, Tsau et al have modified the Ni47.5Al25Fe27.5 alloy by microalloying with Nb as the fourth element to improve its strength 10,11 . They found that adding Nb would reduce the volume fraction of interdendritic regions, but caused the γ' precipitates to remain in the γ-matrix of the interdendritic regions during annealing, so the strength was maintained.…”
Section: Introductionmentioning
confidence: 99%